Determinants of Financial Distress in Islamic Banks: Does Firm Size Matter? - Muhammad Zaki As Shafi MT (Journal Of Economic Cluster, 2024)
This study examines the effects of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO) on Financial Distress, with Firm Size as a moderating variable, in Indonesian Sharia Commercial Banks from 2019 to 2023. Using panel data from 10 banks analyzed using the Random Effects Model (REM), the findings reveal that only FDR significantly affects Financial Distress. A key discovery is that Firm Size significantly moderates (weakens) the negative impact of FDR on Financial Distress, providing empirical support for the "Too Big to Fail" theory within the Islamic banking ecosystem. Conversely, NPF and BOPO showed no significant effects, suggesting that capital buffers and restructuring policies effectively mitigated financing risks and inefficiencies during the pandemic. Theoretically, this research contributes to the international Islamic finance literature by demonstrating that asset size is a more critical determinant of liquidity resilience than credit risk in distressed conditions. The global policy implications underscore the necessity for differential regulatory standards for smaller-scale Islamic banks to prevent systemic risks in emerging markets.